Efficacy of autologous melanocytic transplantation by flip-top technique in patients of stable vitiligo - Jyoti Budhwar; S K Malhotra (Pigment International, 2022)
Background: Vitiligo is an acquired disorder of depigmentation. Various surgical modalities are recommended for quicker resolution of lesions in stable cases. Aim and objectives: To study the efficacy of flip-top technique of autologous melanocytic transplantation in a series of 30 patients with stable vitiligo. Materials and Methods: Thirty patients with stable vitiligo, not responding to adequate trial of medicines were taken in this prospective study. After doing complete investigations, including coagulogram, they were subjected to Flip-top technique of autologous melanocytic transplantation, then 15 patients were put on PUVASOL and 15 patients were exposed to sunlight alone for 3 months. Digital photographs were taken at every sitting. An analysis was performed using the Wilcoxon signed-rank test and Mann--Whitney tests and grading was done for response. Results: Satisfactory cosmetic results were obtained in all cases with 26 patients achieving more than 25% of repigmentation and only 4 patients achieving less than 50% or above repigmentation. Colour match was good with minimal complications. Conclusion: Flip-top technique of autologous melanocytic transplantation appears to be a promising option for patients with stable recalcitrant vitiligo.